2019
DOI: 10.1249/fit.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

China Survey of Fitness Trends for 2020

Abstract: Apply It! • Nation specificity of fitness trends should be considered by international fitness organizations or companies when making strategic plans in other countries. • Ten trends can be recognized as the current stable trends within the health/fitness industry in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 13 publications
5
21
0
1
Order By: Relevance
“…Specifically, personal training was ranked #1 in the present study, which is an outcome totally aligned with the primary finding observed in Europe [16]. In addition, this particular trend appears to be popular worldwide as the fifth most attractive fitness trend [14] while it was ranked #3 in North America [15], #4 in Brazil and Argentina [18], #7 in Spain [19], and #8 in China [17]. Fitness services focused on personal training seem to be significantly popular for Europeans and thus almost 3 out of 4 of the offered exercise services are traditional one-on-one training sessions [20].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Specifically, personal training was ranked #1 in the present study, which is an outcome totally aligned with the primary finding observed in Europe [16]. In addition, this particular trend appears to be popular worldwide as the fifth most attractive fitness trend [14] while it was ranked #3 in North America [15], #4 in Brazil and Argentina [18], #7 in Spain [19], and #8 in China [17]. Fitness services focused on personal training seem to be significantly popular for Europeans and thus almost 3 out of 4 of the offered exercise services are traditional one-on-one training sessions [20].…”
Section: Discussionsupporting
confidence: 86%
“…Considering the fact that several lifestyle-related chronic diseases are currently increasing in Greece [9], our findings these outcomes may be an interesting sign for the future state of the national fitness industry highlighting the pivotal role of fitness practitioners and businesses in public health. Additionally, these outcomes corroborate the majority of the literature showing that 25%-35% of top 20 fitness trends are associated with exercise training for special populations and thus health-related trends systematically gain popularity in the global fitness industry [14,[16][17][18]. Taking these findings into account, it seems that the local fitness industry supports the scientific evidence underlining the critical role of structured exercise in health, performance and quality of life of individuals suffered from chronic conditions [34], including adults [35], and children with obesity [36] as well as elderly [37] and persons who regularly exercise in a clinical setting [13].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations